The Merger of State-Owned Enterprises of Bank Syariah Indonesia in Positive Legal Review and Maqashid Syariah - Hidayat, Sholihul; Fageh, Achmad (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2022)
As a form of the government's participation in paying attention to and developing the market share of the Islamic economy in Indonesia, the three state-owned Islamic banks (BNI Syariah, BRI Syariah, and Mandiri Syariah) were merged into one. With the hope of being able to expand the Islamic banking market both nationally and internationally. This study aims to examine the merger of the three state-owned Islamic banks in terms of positive Law in it and to review it from the perspective of Maqashid sharia. This study uses a qualitative descriptive method by using secondary data obtained through a literature review with references from books, journals, and other literature related to this research. The results of this study indicate that the merger of state-owned banks, Bank Syariah Indonesia, is on the right track, legally positive, and in terms of Maqashid sharia. This is a step and effort by the government in maintaining and developing sharia market share in line with the maqashid sharia principle; keep and or attract good and keep away bad. In addition, some of them are launching a literacy program in understanding the concept of Islamic economics for the community so that the noble values ​​of Islam are maintained and run in banking economic activities. However, it still requires other developments in the aspect of justice that must be initiated by BSI, of course, by continuing to carry the message of sharia in it.